1. Zapisz w jak najprostszej postaci:
a) 3(a+b)+(a-2b)=
b) -4(x-z)-(x+y)=
c) 5(4x-7)+(7-4x)=
d) (4x-y)-2(x+y)=



Odpowiedź :

Glosia
a) 3a + 3b + a -2b=4a+b
b) -4x +4z -x+ y= -5x+4z+y
c) 20x -35 +7- 4x= 16x- 28
d) 4x -y -2x -2y= 2x- 3y
Zdaje mi się, że tak ;)
DOdiii
a. 3a+3b+a-2b=3a+a+3b-2b=4a+b
b. -4x+4z-x-y=-4x-x+4z-y=-5x+4z-y
c. 20x-35+7-4x=20x-4x-35+7=16x-28
d.4x-y-2x-2y=4x-2x-y-2y=2x-3y
a. 3a+3b+a-2b=3a+a+3b-2b=4a+b
b. -4x+4z-x-y=-4x-x+4z-y=-5x+4z-y
c. 20x-35+7-4x=20x-4x-35+7=16x-28
d.4x-y-2x-2y=4x-2x-y-2y=2x-3y

mi sie zdaje ze tak